Pengaruh Kompetensi, Motivasi dan Beban Kerja terhadap Kinerja Perawat IGD RSUD Jatisampurna - Huswatun Hasanah; Eddy Hermawan Hasudungan Panjaitan; Nurwulan Kusuma Devi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Huswatun Hasanah, Nursing care given to patients is assessed as nurse performance. Achievement of good performance is supported by high motivation, competence possessed by nurses, and reduced workload that is the responsibility of nurses. This study aims to analyze the effect of motivation, competence and workload on the performance of nurses at RSUD Jatisampurna.Method: This study uses a quantitative research type with a cross- sectional approach. The sampling technique in this study is a saturated sample with a total of 35 nurses. The instrument in the study used a questionnaire. The data analysis technique used is the analysis used multiple linear regression. Research with N = 35 through the T Test showed that t count > t table or 46.839 > 2.032 with a significance value of 0.001 < 0.05, meaning that Competence (X1) has a significant effect on the performance of nurses Through the T Test, it shows that t count > t table or 44.424 > 2.032 with a significance value of 0.001 < 0.05, meaning that motivation (X2) has a significant effect on on the performance of nurses. Through the T Test, it shows that t count > t table or 14.375 > 2.032 with a significance value of 0.001 < 0.05, meaning that workload (X3) has a significant effect on on the performance of nurses. Through the F Test with f count > f table or 1.29.074014 > 4.12 with a significance level of 0.00 < 0.05, this means that simultaneously there is an Competence, motivation and workload jointly influence the performance of nurses. Competence influences nurses performance, Competence influences nurses performance, motivation influences nurses performance, and workload influences nurses performance. Competence, motivation and workload jointly influence the performance of nurses.